Pengenalan Kue Klepon Sebagai Warisan Kuliner Nusantara dalam Upaya Pelastarian Budaya di Tengah Masyarakat Kelurahan Selumit Pantai - Nurul Hidayat; Sisna Fiani; Bunga Bunga; Gloritio Xander; Yilka Jeni Bidang; Wenie Octavianty Dayang (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
Klepon is a traditional Indonesian market snack made from glutinous rice flour, shaped into small balls, and filled with sweet palm sugar, then coated with savory grated coconut. When bitten, the palm sugar inside bursts, giving a unique and delicious taste sensation. Klepon has been part of the Nusantara culinary heritage since the 1950s and was even introduced by Indonesian immigrants to the Netherlands. According to Mangkubumi, modifying the klepon recipe is an effective way to introduce and preserve this traditional food, as long as the original recipe and shape are maintained. This way, people can still enjoy klepon in its original form even though there are modern variations like klepon cake.